LINKING FINANCIAL LITERACY LIFESTYLE AND SELF-CONTROL TO PERSONAL FINANCIAL MANAGEMENT IN HIGHER EDUCATION STUDENTS - Sirait, Cornella Sari; Takidah, Erika; Sumiati, Ati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This research seeks to examine several key relationships: (1) how financial literacy affects personal financial management, (2) how lifestyle affects personal financial management, (3) how self-control affects personal financial management, and (4) how financial literacy, lifestyle, and self-control together influence personal financial management. The study adopts a quantitative research design through the use of survey methods, involving a total of 279 respondents. Data were gathered using a structured questionnaire based on a Likert scale. The analytical technique employed is multiple regression analysis. The research results show that financial literacy, lifestyle, and self-control significantly influence personal financial management, both partially and simultaneously. These results suggest that improving financial literacy, fostering a planned lifestyle, and developing self-control can help students better manage their personal finances.